2006
DOI: 10.1007/s00264-006-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement in patients with severe bleeding disorders

Abstract: Arthropathy of the hip is moderate in frequency in haemophiliac patients, but is less common than ankle, knee or elbow arthropathy. We report about our experience with total hip replacement in patients with severe bleeding disorders over a period of 30 years. Between July 1972 and 2002, 15 hips in 13 patients were replaced. The main bleeding disorders were Haemophilia A in ten patients and severe v. Willebrand disease in three patients. The mean follow-up was 132 months (range 12-363). We can demonstrate good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…They demonstrated good long-term results, with only one aseptic loosening after 14 years and one septic loosening after 14 months in a HIV-positive patient. The Harris Hip Score increased from 48 points (32-66) preoperatively to 89 (76-100) postoperatively [27].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated good long-term results, with only one aseptic loosening after 14 years and one septic loosening after 14 months in a HIV-positive patient. The Harris Hip Score increased from 48 points (32-66) preoperatively to 89 (76-100) postoperatively [27].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in concordance with other reviews that have concluded there is strong correlation between mental health parameters, including anxiety, depression and catastrophization and persistent postoperative pain, along with female sex and younger age 14 . These factors may explain the generally better results from case series of arthroplasty in haemophlia patients compared to studies of the general population 15,16 . This is despite haemophilia patients being younger, with worse functional status and similar pre-operatively pain scores, but importantly significantly less mental health disease, SF36, 70.2 vs. 60.2 respectively 17,18 .…”
Section: S-0805mentioning
confidence: 98%
“…5 (range:[10][11][12][13][14][15][16][17][18][19][20][21][22]. Results: No failures and no complications were recorded at a mean follow-up of 8.1 years (range: 2.1-13.7 years).…”
mentioning
confidence: 99%
“…However, this was without any reference to what ''normal'' blood loss was, or what the total amount was for the haemophilia patients. 20,21 In a more comprehensive study, Yoo et al objectively measured blood loss in group of 23 patients undergoing THA for end-stage haemophilic arthropathy and found that mean blood transfusion requirements intraoperatively were 1.5 units (range 0-5 units) of packed red cells and 0.5 units (range 0-5 units) of fresh frozen plasma (FFP), and mean of 1.33 units (range 0-3 units) of packed red cells in the postoperative period with one patient requiring ''massive transfusion'' despite adequate pre-operative factor levels. 22 Nelson et al state that the range of blood loss in a group of 38 patients with haemophilia was 300-1000 ml, but they did not report a mean value, which makes this hard to interpret.…”
Section: Discussionmentioning
confidence: 99%